The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods. (January 2023) - An, Bai-Hong; Xu, Da-Mao; Geng, Rui; Cheng, Yan; Qian, Rui-Bo; Tang, Xian-Chun; Fan, Zhi-Qiang; Chen, Hong-Bin
Abstract: To prevent the scale formation in the equipments and pipelines after pre-treated coal gasification gray water (CGGW) entering the reuse system and reduce the influence of various pollutants in the effluent on subsequent biochemical treatment, this study presented a coupled use of pulse electrocoagulation (PEC) and chemical precipitation (CP) coupling method for the pretreatment of coal gasification gray water (CGGW). In addition, the operation parameters of PEC and the reaction conditions of PEC–CP were optimized based on iron plate as electrode and total hardness, turbidity and sludge yield as assessment indicators. Due to the formation of multi-hydroxyl iron by several minutes of pulse current, and the addition of pH regulator and coagulant aid, the efficient removal of various ions, hardness and turbidity was significantly reduced via various mechanism such as redox, precipitation, adsorption and coagulation reaction. The result indicated that under the optimal operation conditions, the total hardness, turbidity, and Fe n+ of PEC–CP effluents were 275.0 mg/L, 3.0 NTU and 5.6 mg/L, respectively and sludge amount was 0.88 kg/m 3 . The removal rates of Si, B, Mn, Ba, COD, NPOC and NH4 + –N by PEC–CP reached 80.0%, 75.4%, 97.0%, 99.8%, 35.0%, 33.6% and 23.8%, respectively. The present results suggested that the CGGW pretreatment effluents could be not only reused directly, but also greatly alleviate the scaling problem of water pipeline and coal gasification production facilities. Graphical abstract: Image 1 Highlights: The PEC–CP was employed for coal gasification gray water (CGGW) pretreatment. PEC–CP removed over 80.0%, 75.4%, 97.0%, 99.8% of Si, B, Mn, Ba. The pretreatment mechanism was proposed based on multidisciplinary characterization. The reuse of CGGW was realized with low pretreatment costs.